Effect of adhesive sealant on resistance spot welding of 301L stainless steel. (March 2020) - Sun, Xiaoguang; Zhang, Qingxin; Wang, Suhuan; Han, Xiaohui; Li, Yongbing; David, Stan A.
Abstract: To solve the poor sealing performance of stainless-steel metro car bodies, a non-curing sealant is introduced into the resistance spot welding (RSW) process. Effects of the sealant on the weldability, mechanical property, and failure mode of 301L austenitic stainless steel (ASS) RSW welds were systematically investigated in this work. Under the action of electrode pressure, the sealant gathers around the quasi-nugget zone and leaves a thin residual sealant layer between the substrates. The insulating sealant leads to an earlier nugget initiation, a bigger nugget size and a higher heat utilization ratio than the traditional RSW process. The thermal decomposition products spread to the nugget and exist in the form of pores and inclusions. The proportion of residual δ -ferrite is decreased due to the long-lasting heat preservation effect of the surrounding sealant. The tensile strengths and failure mode of resistance spot welds with sealant (S-RSW) are undesired, resulting from the local softening and dispersedly distributed gas pore and inclusion defects. However, the adverse effects of the sealant on mechanical performances could be eliminated by appropriate increasing welding current. Considering the markedly improved sealing performance, S-RSW would be a useful and valuable process in engineering applications.